Nacionalismo militarista cotidiano en las escuelas de la dictadura chilena: usos rituales de los actos cívicos y las efemérides (1973-1980) - Sebastián Neut Aguayo; Pablo Neut Aguayo (Historia Crítica)
Objective: This article analyzes how the Chilean dictatorship tried to instill a militaristic nationalism in the country’s school’s daily life, showing how this nationalism was reappropriated and, in some cases, resisted by part of the student body and the teaching staff. This approach is based on the study of civic events and the commemoration of school anniversaries between 1973 and 1980. Methodology: We proceed to the triangulation between different primary materials, specifically, the magazine Revista de Educación of the Ministry of Education, declassified documents referring to internal communications of the dictatorship on educational matters (as well as on the repression in this field), materials from the academic archives of the Instituto Nacional and the Liceo Javiera Carrera, judicial records and interviews with teachers and students of the time. Originality:The crossing of the theories of nationalism and daily school life is used, and it is found that the dictatorship produced a new grammar of educationalization that profoundly impacted the school culture. This was characterized by the display of a profound military-nationalist ritualization. Unlike other studies on the period, attention is paid to the ideological use and daily expression of school rituals and the transgressions carried out in the ritual dimension. Conclusions: The attempt to implant a military-nationalist vision through daily school rituals was relatively successful since, while part of the students naturalized the existence of such military-nationalism, another part opposed it through the transgression/resistance of the very rituality that promoted it. This last shows the existence of a conflictive dimension of school culture.